2016
DOI: 10.1186/s12986-016-0098-6
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction between FTO gene variants and lifestyle factors on metabolic traits in an Asian Indian population

Abstract: BackgroundLifestyle factors such as diet and physical activity have been shown to modify the association between fat mass and obesity–associated (FTO) gene variants and metabolic traits in several populations; however, there are no gene-lifestyle interaction studies, to date, among Asian Indians living in India. In this study, we examined whether dietary factors and physical activity modified the association between two FTO single nucleotide polymorphisms (rs8050136 and rs11076023) (SNPs) and obesity traits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 51 publications
0
62
3
2
Order By: Relevance
“…Source: Vimaleswaran et al . (). (b) Interaction of the FTO gene polymorphism (rs11076023) with dietary fibre intake on BMI in Asian Indians.…”
Section: Findings From Genuine Collaborationmentioning
confidence: 97%
See 1 more Smart Citation
“…Source: Vimaleswaran et al . (). (b) Interaction of the FTO gene polymorphism (rs11076023) with dietary fibre intake on BMI in Asian Indians.…”
Section: Findings From Genuine Collaborationmentioning
confidence: 97%
“…Our study (Vimaleswaran et al . ) identified a significant interaction between FTO SNP rs8050136 and carbohydrate intake (% energy) ( P interaction = 0.04), where the ‘A’ allele (the high‐obesity‐risk variant of the FTO gene) carriers had 2.46 times increased risk of obesity than those with low‐obesity‐risk ‘CC’ genotype ( P = 3.0 × 10 −5 ) among individuals in the highest tertile of carbohydrate intake (% energy; mean: 71%). A significant interaction was also observed between FTO SNP rs11076023 and dietary fibre intake ( P interaction = 0.0008), where individuals with AA genotype in the 3rd tertile of dietary fibre intake had, on average, 1.62 cm lower waist circumference than those with low‐obesity‐risk ‘T’ allele ( P = 0.02) (Fig.…”
Section: Findings From Genuine Collaborationmentioning
confidence: 99%
“…Previous interaction studies on BMI‐related genetic variants and lifestyle factors highlight the importance of modifying diet and physical activity to decrease high BMI risk in genetically predisposed individuals (Celis‐Morales et al, ; Vimaleswaran et al, ). Another possible factor that may modify genetic susceptibility to high BMI is comorbid depression.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies shown above have been conducted in individuals of European ancestry. However, the effects of FTO and its interaction with either protein or fat intake on BMI seems to expand across ethnicities to Asian Indians (33). …”
Section: Introductionmentioning
confidence: 99%
“…Using individual FTO SNPs and GRS created with FTO SNPs, the authors found that the association of FTO variants with BMI was stronger in individuals who consumed high levels of dietary fiber. Individuals with AA of rs11076023 (33) and TT and AT of rs3751812 (34) had lower abdominal obesity or waist circumference in those who had the highest fiber intake (33,34). A member of the superfamily of non-haem-Fe(II) and 2-oxoglutarate (2OG)-dependent dioxygenases, FTO is believed to be involved in regulation of energy intake with a key role in nervous and cardiovascular system (35,36).…”
Section: Introductionmentioning
confidence: 99%